Civil Defense Performance in the Evaluation and Analysis of Environmental Risks - Santos, Daris Correia dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The procedures used in risk assessment differ according to the nature of the phenomenon addressed, because the risk assessment involves information relating to projects implemented and their possible consequences. Analysis activities and sectorization risk of destabilization of slopes processes undertaken in November 2011 and February 2012 surveys consisted of techniques for the identification of critical points, risks and vulnerabilities thus helping the actions taken by the Civil Defense and evaluation of achievement preventive works according to the potential environmental effects of the risk areas and the degree of reversibility of environmental impacts for urban squatter settlements called neighborhood Ivaldolândia, Conjunto Vida Nova, Mazagão and Mutirão located in the Municipality of Alagoa Nova, PB, Brazil. The analysis of environmental risks and impacts involved the delineation of the study area, identifying the type of geodynamic processes, risk mapping and elaboration of the Leopold matrix. Through the analysis of the environmental impacts relevant risk areas of the city of Alagoa Nova Paraíba is possible to adopt mitigation measures and assess the importance, magnitude and frequency that such events occur. It appears that the stabilization of soil slopes and retaining walls using vegetation and the removal of people from critical areas minimize the vulnerability of the population. The position of the housing relative to the inclination of the slope generates risk which makes it imperative to avoid drastic changes in topography and observe the minimum clearances established along the slopes.